THE INFLUENCE OF WORK ON THE MENTAL HEALTH OF SPECIAL EDUCATION TEACHERS - Gomes do Nascimento, Mysllene; Lima do Nascimento, Crisóstomo (LINKSCIENCEPLACE, 2025)
Nowadays, in the contemporary world, society has been experiencing massive transformations, and the number of students with some disability or disorder has increased. In the given context, Multifunctional Room teachers face a series of issues, including the absence of public policies aiming their health and well-being. The purpose of this research is to understand the challenges and needs of teachers of Specialized Educational Support Services by presenting strategies to improve the well-being and life quality of teachers and students. The idea is to provide high-quality teaching and a healthier school environment. To write this study, it was conducted a literature review of scientific papers on the subject based on authors such as Montoan (2015), the Legal Political Frameworks of Special Education to Inclusive Education (2010), and the National Law of Curricular Guidelines and Educational Framework (2023). It is essential that attitudes towards caring and valuing these professionals are adopted to promote changes that allow greater equality, equity, and respect in the school environment.